Poverty in Nobsa crisis and challenges (2021)
As one of the many consequences left by the current pandemic and the current socio-economic problem that is being experienced worldwide, the concept of “poverty” can be taken as a symbol that represents the majority of the families hit by this crisis, revealing more forcefully that there are economic inequalities in our community, mainly lacking basic services (decent housing, education, well-being, food, health, etc.). This can be classified into different types according to the factors that influence the origin of this qualifier, leading to an interest in inquiring about the indices that have determined poverty, five years before and those that are evident after living this COVID- 19 pandemic , in the municipality of Nobsa. Through a documentary, historical, comparative and analytical investigation, it will be determined which population group and which sectors were the most affected, forging strategies from the municipal government to mitigate this problem.